Active DNA Demethylase, TET1, Increases Oxidative Phosphorylation and Sensitizes Ovarian Cancer Stem Cells to Mitochondrial Complex I Inhibitor - Lin-Yu Chen; Yao-An Shen; Ling-Hui Chu; Po-Hsuan Su; Hui-Chen Wang; Yu-Chun Weng; Shiou-Fu Lin; Kuo-Chang Wen; Phui-Ly Liew; Hung-Cheng Lai (MDPI AG, 2024)
Ten-eleven translocation 1 (TET1) is a methylcytosine dioxygenase involved in active DNA demethylation. In our previous study, we demonstrated that TET1 reprogrammed the ovarian cancer epigenome, increased stem properties, and activated various regulatory networks, including metabolic networks. However, the role of TET1 in cancer metabolism remains poorly understood. Herein, we uncovered a demethylated metabolic gene network, especially oxidative phosphorylation (OXPHOS). Contrary to the concept of the Warburg effect in cancer cells, TET1 increased energy production mainly using OXPHOS rather than using glycolysis. Notably, TET1 increased the mitochondrial mass and DNA copy number. TET1 also activated mitochondrial biogenesis genes and adenosine triphosphate production. However, the reactive oxygen species levels were surprisingly decreased. In addition, TET1 increased the basal and maximal respiratory capacities. In an analysis of tricarboxylic acid cycle metabolites, TET1 increased the levels of α-ketoglutarate, which is a coenzyme of TET1 dioxygenase and may provide a positive feedback loop to modify the epigenomic landscape. TET1 also increased the mitochondrial complex I activity. Moreover, the mitochondrial complex I inhibitor, which had synergistic effects with the casein kinase 2 inhibitor, affected ovarian cancer growth. Altogether, TET1-reprogrammed ovarian cancer stem cells shifted the energy source to OXPHOS, which suggested that metabolic intervention might be a novel strategy for ovarian cancer treatment.